2019
DOI: 10.1136/sextrans-2018-053903
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider and service user perspectives on STI risk reduction interventions for young people and MSM in the UK

Abstract: ObjectiveBehavioural interventions have been shown to reduce sexual behaviours associated with increased risk of sexually transmitted infections in young people (<25 years) and men who have sex with men (MSM) internationally, but evidence from England is limited. We aimed to explore service provider and user experiences and perspectives on behavioural interventions to reduce sexual behaviour risks, and the use of automated methods to triage individuals to these services.MethodsWe conducted a sequential mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…The current behavior interventions or services for HIV prevention among MSM mainly focus on providing health packages, such as condoms and AIDS testing kits, videos, and digital interventions (e.g., using apps) [ 32 , 33 ]. However, if the scope of behavior interventions excluded the psychological factors, it would be difficult to achieve the intervention goals.…”
Section: Discussionmentioning
confidence: 99%
“…The current behavior interventions or services for HIV prevention among MSM mainly focus on providing health packages, such as condoms and AIDS testing kits, videos, and digital interventions (e.g., using apps) [ 32 , 33 ]. However, if the scope of behavior interventions excluded the psychological factors, it would be difficult to achieve the intervention goals.…”
Section: Discussionmentioning
confidence: 99%
“…Our model results showed that targeting behavioural interventions at all tested high-risk individuals, including both individuals who tested chlamydia positive as well as those who tested negative, should be a part of STI management as well in order to reduce chlamydia prevalence most effectively. However, as sufficient resources to deliver behavioural interventions face-to-face to all tested individuals (e.g., during an STI test consultation) are often not available, online interventions might be a good alternative 34 , 59 , 60 . For example, a validated set of questions to assess certain psychological characteristics may be added to the process of making an appointment online (i.e., before testing).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a validated set of questions to assess certain psychological characteristics may be added to the process of making an appointment online (i.e., before testing). This extra information could be used to deliver tailored online interventions at the SHC, such as a video-based intervention during the online intake assessment, or after retrieving the chlamydia test results online 34 , 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary prevention of chlamydia infection is usually aimed at achieving riskreducing behaviour, such as promotion of condom use [2], and behaviour change might be vital part of chlamydia control [43,44]. Extensive data on changes in sexual behaviour, psychosocial determinants, and STI/HIV infections over time have been collected in longitudinal cohort studies among men who have sex with men (MSM) [81][82][83][84][85][86][87][88]. However, among young heterosexual males and females, few published data are available on multiple psychological and behavioural characteristics, and chlamydia infections at more than one follow-up moment [20,39,85,89].…”
Section: Longi T U Dina L Cohort St U Dy a Mong You Ng H Et Erosex-ua Ls -T H E Im Pact St U Dymentioning
confidence: 99%